2021
DOI: 10.1111/josh.12992
|View full text |Cite
|
Sign up to set email alerts
|

Current Asthma Management Practices by Primary School Teaching Staff: A Systematic Review

Abstract: BACKGROUND The likelihood of children with asthma experiencing an exacerbation at school is significantly high when considering that they spend a substantial part of their day at school. This study, therefore, aimed to systematically review the literature to determine current asthma management practices by primary school teaching staff and any existing supporting legislation/policies/guidelines. METHODS Search terms were adapted to search literature across databases: CINAHL, Cochrane Library, Education Databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
2
3
0
3
Order By: Relevance
“…Children's lack of access to their inhalers while at school has commonly been identified as a barrier to appropriate use of their inhaler [46][47][48][49] . Parents also reported that teachers were not always knowledgeable about asthma and their child's asthma management plan, in agreement with previous research 45,46,51 Building on existing literature 22 , [51][52][53][54] , future research may seek to more fully assess the perspectives of key stakeholders such as governing councils, school nurses and teachers. This research is needed to design and test solutions, particularly regarding access to children's inhalers.…”
Section: Discussionsupporting
confidence: 80%
“…Children's lack of access to their inhalers while at school has commonly been identified as a barrier to appropriate use of their inhaler [46][47][48][49] . Parents also reported that teachers were not always knowledgeable about asthma and their child's asthma management plan, in agreement with previous research 45,46,51 Building on existing literature 22 , [51][52][53][54] , future research may seek to more fully assess the perspectives of key stakeholders such as governing councils, school nurses and teachers. This research is needed to design and test solutions, particularly regarding access to children's inhalers.…”
Section: Discussionsupporting
confidence: 80%
“…According to some testimonials from teachers, communication is flawed, resulting in teachers not knowing about the child’s asthma diagnosis, increasing fear and insecurity in the face of the disease’s worsening condition. Similar results were found in studies that made up a systematic review on the subject, with the conclusions reinforcing the importance of effective communication between school, family, and health professionals ( 9 ) .…”
Section: Discussionsupporting
confidence: 80%
“…The low rate of correct answers to open questions regarding medications was also identified in a recent systematic review on the subject. Of the 13 studies analyzed, six indicated low knowledge of teachers about medications for treating asthma exacerbations ( 9 ) . A possible hypothesis to explain this finding is that open questions present a higher degree of difficulty when compared to multiple-choice questions, which can be answered randomly and, consequently, with a greater possibility of correct answers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in keeping with the previous studies. [9,14,18,19,30] The triggers, especially the common ones such as smoke, strong odor, and dust, are easier to understand by teachers compared to the aspect related to etiology, pathogenesis or management. Good knowledge of the various triggers of asthma, especially those poorly known, such as cockroaches, feathers, and fur, is crucial, so the teacher is proactive in preventing asthma attacks by identifying likely triggers in the school environment.…”
Section: Discussionmentioning
confidence: 99%